(untitled) (International journal of artificial intelligence, 2026)
This article examines the phenomenon of the linguaculturological concept, its theoretical underpinnings, and its significance in contemporary linguistic research. The study highlights key methodologies for analyzing linguaculturological concepts and discusses their implications for cross-cultural communication, translation studies, language teaching and learning, and cognitive linguistics.